Paciente de 33 años de edad con preeclampsia severa en el Hospital gineco - obstétrico Matilde Hidalgo de Procel - Cobeña Vélez, Edith Marilexy (2018)
Pre-eclampsia (PEE) is a specific disease of pregnancy. Which occurs with increased blood pressure accompanied by proteinuria (greater than or equal to 3 grams in a 24-hour period), edema or both at the same time, and which usually appears between 20 weeks of gestation and 24 hours after Birth. When this condition is accompanied by seizures and CNS symptoms, we are in the presence of Eclampsia (ECL). After having completed the process of nursing care, we were able to learn more about the pathology "Severe preeclampsia" and all the complications that can be caused in a practical way. Likewise, the nursing interventions were carried out according to the needs that the patient required in order to achieve a prompt recovery